Editorial for the Special Issue: "Honey Bee Products as an Alternative or Complement to Classical Antibiotics" - Piotr Szweda (MDPI AG, 2021)
Based on World Health Organization reports, the resistance of bacteria to well-known antibiotics is becoming a major global health challenge [...]